Bangladesh and Pakistan: The Great Divergence (The Pakistan Development Review, 2020)
There was a time when Bangladesh lagged behind Pakistan in the quality of life measured by any of its major indicators, except for adult literacy and schooling of children. But it is a different story today. Bangladesh is ahead of Pakistan in almost every respect. I intend to present the facts (data) to support this proposition first and then explore the reasons for the great divergence. I am far more certain about the evidence than I am of my explanation since some of it is guesswork, though hopefully not too off the mark.